Rapid volumetric additive manufacturing in solid-state : a case study using thermal gel - Faqrul Hasif Abdul Nasir (Nanyang Technological University, 2021)
There has been significant progress in the development of additive manufacturing (AM) - widely known as three-dimensional (3D) printing - since its introduction in the late 1980s. In recent developments, new ‘smart’ materials have been shown to possess the ability to change shape with external stimulants added to them, giving rise to the term ‘4D Printing’. One example would be Hydrogels, having been researched and studied extensively and have shown promising signs for possible future biomedical applications due to its biocompatibility and Shape Memory Effect (SME). However, extensive research has yet to be conducted to study the 3D printing methods for Hydrogel; that could potentially produce complex shapes for applications in the biomedical fields or in areas of unstable environment/micro gravity. This report is aimed at studying a method of Hydrogel 3D printing: which is a modified Stereolithography Apparatus (SLA) / Masked SLA printing method. Additionally, the report will place emphasis on proving the concept of the modified SLA method and the many factors to consider. Principles and characteristics learnt from exploring the modified SLA method, will be used to guide further development of the Modified FDM method in future studies. The initial stage of the study would be familiarizing the hydrogel preparations, noting the characteristics and factors to ensure quality results. The subsequent stages would be focused on proving the concept of SLA method printing in solid state, enabled by the unique characteristic of Hydrogel. Analysis and conclusions will be drawn from the results, alluding to the possible effect that UV cross-linking has on refractive index, consequently affecting print quality.